TELAAH KRITIS ETIKA BISNIS DALAM PERSPEKTIF ISLAM (KONSEP DAN IMPLEMENTASI PADA PELAKU USAHA) - Mubarok, Farhan Zaki; Fadjar, Nurman Setiawan (Islamic Economics and finance in Focus, 2024)
This research aims to find out the concept of Islamic business process flow involving financing, production, and marketing within the scope of business ethics. The researcher uses the literature review method in examining Islamic business ethics by looking at the process of financing, production, and marketing as well as comparing with conventional business ethics to get a comparison of views between business ethics seen from various related literature sources. The results of this research show that the concept of Islamic business ethics can be a reference and choice for business people who want to run a business to achieve prosperity in order to be blessed in the world and the hereafter.